2021
DOI: 10.1108/ejim-09-2020-0345
|View full text |Cite
|
Sign up to set email alerts
|

Green market orientation, green innovation capability, green knowledge acquisition and green brand positioning as determinants of new product success

Abstract: PurposeThe purpose of this study is to assess if the mediating effect of green innovation capability (GIC) in the relationship between green market orientation (GMO) and new product success (NPS) was conditional on the moderating effects of green knowledge acquisition (GKA) and green brand positioning (GBP).Design/methodology/approachThe analysis was based on primary data gathered using a structured questionnaire, which was developed on a five-point Likert scale of 1-Strongly disagree to 5-Strongly agree. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 71 publications
(119 reference statements)
0
61
0
Order By: Relevance
“…Several studies in the literature have confirmed that the positive relationship between big data analytics capabilities and green innovation is still in its early stages (Mani et al, 2017). However, available empirical studies on this relationship have proven positive and direct effects of big data analytics capabilities on promoting green innovation (Imran et al, 2021;Waqas et al, 2021;Yaoteng and Xin, 2022) through using these technological and human capabilities in maximizing benefit and improving the efficiency of operational processes within factories and transportation methods, leading to reduced waste (Borah et al, 2021) and thus introducing more environmentally-related innovations (Mavi and Mavi, 2021). Tools used in big data analytics help to enhance green innovation capabilities within firms (Beier et al, 2022;Dong et al, 2022), and they provide accurate predictive tools that can be used in developing new environmental ideas that the firm may use in the future in developing green innovations (Bag et al, 2020;Meiyou and Ye, 2022).…”
Section: The Relationship Between Big Data Analytics Capabilities And...mentioning
confidence: 99%
“…Several studies in the literature have confirmed that the positive relationship between big data analytics capabilities and green innovation is still in its early stages (Mani et al, 2017). However, available empirical studies on this relationship have proven positive and direct effects of big data analytics capabilities on promoting green innovation (Imran et al, 2021;Waqas et al, 2021;Yaoteng and Xin, 2022) through using these technological and human capabilities in maximizing benefit and improving the efficiency of operational processes within factories and transportation methods, leading to reduced waste (Borah et al, 2021) and thus introducing more environmentally-related innovations (Mavi and Mavi, 2021). Tools used in big data analytics help to enhance green innovation capabilities within firms (Beier et al, 2022;Dong et al, 2022), and they provide accurate predictive tools that can be used in developing new environmental ideas that the firm may use in the future in developing green innovations (Bag et al, 2020;Meiyou and Ye, 2022).…”
Section: The Relationship Between Big Data Analytics Capabilities And...mentioning
confidence: 99%
“…In many researches green brand positing is treated as uni-dimensional variable (Aulina & Yuliati, 2017; Baiquni & Ishak, 2019; Himawan, 2019; Tristiani et al, 2019). In recent years, this variable is still considered as a single construct instead of a multidimensional construct (Borah et al, 2021; Pebrianti & Aulia, 2021; Situmorang et al, 2021). The current study uses the green brand positioning as a uni-dimensional construct based on these facts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When the correlation coefficients derived from both analysis (before and after controlling for the marker variable) are significantly different from each other, CMB is said to be present in the dataset. From Table 2, we conclude that there was no CMB in our dataset, as both the correlation scores from the restricted and unrestricted estimations were not significantly different from each other (Borah et al. , 2021).…”
Section: Methodsmentioning
confidence: 76%
“…That is, the square root of AVEs were larger than the inter-correlation coefficients. The study also assessed multicollinearity (Borah et al. , 2021) by assessing the correlation coefficients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation